2019
DOI: 10.1146/annurev-soc-073018-022424
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Destinies: Children of Immigrants Growing Up in the United States

Abstract: More than a quarter century of research has generated fruitful results and new insights into the understanding of the lived experiences of the new second generation, which broadly includes both native-born and foreign-born children of immigrant parentage. We critically review the burgeoning literature on the divergent trajectories and unequal outcomes of this new second generation. Given recent changes in immigration policy and in contexts of both exit and reception for new immigrants, we pay special attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 83 publications
0
28
0
Order By: Relevance
“…The authors argue that this reflects the higher concentration of social capital within the ethnic group. A wealth of research in this tradition has since found ethnic social capital, or ' ethnic capital', to be associated with higher educational aspirations for children of immigrants in the USA -particularly among youth with Asian background (Khachikian & Bandelj 2019;Zhou & Gonzales 2019). However, much of this research has been qualitative or has compared migrants with different legal statuses from the same region of origin.…”
Section: Previous Researchmentioning
confidence: 99%
“…The authors argue that this reflects the higher concentration of social capital within the ethnic group. A wealth of research in this tradition has since found ethnic social capital, or ' ethnic capital', to be associated with higher educational aspirations for children of immigrants in the USA -particularly among youth with Asian background (Khachikian & Bandelj 2019;Zhou & Gonzales 2019). However, much of this research has been qualitative or has compared migrants with different legal statuses from the same region of origin.…”
Section: Previous Researchmentioning
confidence: 99%
“…The value of these stories emerges from the words written by these successful students: by writing their autobiographies, they have voice as authors of their own educational experience, reflecting on their life without simplification or reductionism. After all, these autobiographies highlight that the different cohorts of immigrantorigin students are in a much more complex and ambivalent situation than what merely pessimistic or optimistic interpretations can truly explain (Zhou and Gonzales 2019).…”
Section: Discussionmentioning
confidence: 97%
“…This program provided eligible undocumented individuals permission to legally work in the United States and deemed them low priority for deportation. Eligible individuals received a work authorization card and a social security number, and gained access to resources that could improve their social and economic incorporation: they could apply for driver's licenses, gain health insurance, develop credit, and apply for Advanced Parole (Zhou and Gonzales 2019;Gonzales et al 2014). If granted Advanced Parole, DACA recipients may have the opportunity to deepen relationships with family in their home countries if traveling for humanitarian, emergency, or educational reasons (Ruth et al 2019).…”
Section: Mental Health and Dacamented Statusmentioning
confidence: 99%